Penghayatan Terhadap Kebhinekatunggalika-an dan Nilai-Nilai Pancasila di SMAN 10 Palembang dalam Menguatkan Identitas Manusia Indonesia - Patmawati (Amal Insani Foundation, 2023)
Pancasila and Bhinneka Tunggal Ika are two very important values for the Indonesian nation. Both emphasize the importance of tolerance and unity in Indonesia and are very important things to have in strengthening Indonesian human identity. This study aims to find out how the appreciation of diversity and the values of Pancasila in strengthening Indonesian human identity are applied at SMAN 10 Palembang. This research is a qualitative research using the methods of observation, interviews and literature studies which will describe how schools carry out an appreciation of diversity and the values of Pancasila. The results of the study show that SMAN 10 Palembang has implemented a school environment that is diverse in diversity and implements Pancasila values well as evidenced by carrying out joint discussion activities, holding clean Friday activities, praying according to each other's beliefs, deliberating in making decisions, acting fairly and mutual respect and respect between educators and students.